Effects of Urotensin II Receptor Antagonist, GSK1440115, in Asthma - Portnoy, Alison D.; Kumar, Sanjay; Behm, David J.; Mahr, Kelly M.; Noble, Robert B.; Throup, John; Russ, Steven F. (Frontiers in Pharmacology, 2013)
Background: Urotensin II (U-II) is highly expressed in the human lung and has been implicated in regulating respiratory physiology in preclinical studies. Our objective was to test antagonism of the urotensin receptor (UT) by GSK1440115, a novel, competitive and selective inhibitor of the UT receptor, as a therapeutic strategy for the treatment of asthma. Methods: Safety, tolerability and pharmacokinetics (PK) of single doses of GSK1440115 (1–750 mg) were assessed in a Phase I, placebo-controlled study in 70 healthy subjects. In a Phase Ib study, 12 asthmatic patients were randomized into a 2-period, single-blind crossover study and treated with single doses of 750 mg GSK1440115 or placebo and given a methacholine challenge. Results: Administration of GSK1440115 was safe and well-tolerated in healthy subjects and asthmatic patients. In both studies, there was a high degree of variability in the observed PK following oral dosing with GSK1440115 at all doses. There was a marked food effect in healthy subjects at the 50 mg dose. In the presence of food at the 750 mg dose, the time to maximal concentration was between 2 and 6 hours and the terminal half-life was short at approximately 2 hours. All asthmatic patients maintained greater than the predicted concentration levels necessary to achieve predicted 96% receptor occupancy for >=3 hours (between 4-7 hours post-dose). There were no apparent trends or relationships between the systemic plasma exposure of GSK1440115 and pharmacodynamic endpoints, PC20 after methacholine challenge and FEV1, in asthmatics. Conclusion: While GSK1440115 was safe and well-tolerated, it did not induce bronchodilation in asthmatics, or protect against methacholine-induced bronchospasm, suggesting that acute UT antagonism is not likely to provide benefit as an acute bronchodilator in this patient population.